PENGALAMAN UMAT DALAM DEVOSI SAKRAMEN MAHAKUDUS DAN MERAYAKAN EKARISTI KUDUS - Tukan, Antonius Ignasius Nggino (STIPAS Keuskupan Agung Kupang, 2020)
This paper reviews the experience of the faithful in practicing devotion and the Holy Eucharist. This paper is the result of processing a simple research on the experience of the people regarding the topic mentioned above (devotion and eucharist). The basic questions in this short research are what are the goals of the people when they make devotions to visit the Blessed Sacrament and also when they celebrate the Eucharist. Why do they carry out these activities? How can their actions be read in a theological-liturgical perspective? The research method used is the phenomenological method and the analysis used in treating the phenomenological data of this research is critical-descriptive analysis. The results obtained from this research are: (1). All interviewed informants revealed that the purpose of participating in adoration activities and Eucharistic celebrations was to calm themselves. (2) Their reason for doing this activity is the spiritual experience experienced.